Self-serving redistributive preferences among natives and immigrants in the UK - Linda Dezsîo; Christian Koch (EcoAustria - Institute for Economic Research, 2024)
In an online experiment, we examine how ingroup bias and fairness concerns shape the redistributive preferences of UK resident natives and immigrants. Natives and immigrants were paired in a series of distributive situations. They chose how to divide a pie created from either party's previous contributions and stated what they believed to be their fair share from the vantage point of UK residents acting as unbiased spectators. In a complementary survey, we obtained these spectator divisions. We found that natives' and immigrants' distributive choices were absent ingroup bias. Their choices were, however, selfishly biased, as they invoked the fact that the pie was created solely from their own contributions. This behavior was eliminated when it disproportionately harmed the partner. Their fairness beliefs showed evidence of egocentric norm adoption: they favored equity as contributors and equality as noncontributors. They also believed that spectators would negatively discriminate against immigrants in favor of natives, but this perception was unfounded in light of spectators' divisions. We discuss the implications of our results for immigration research and integration policies. – – In einem Online-Experiment untersuchen wir, wie Voreingenommenheit und Gerechtigkeitsbedenken, die Umverteilungspräferenzen von in Großbritannien ansässigen Einheimischen und Einwanderern beeinflussen. Einheimische und Einwanderer wurden in einer Reihe von Verteilungssituationen miteinander gepaart. Sie entschieden, wie ein Kuchen, der aus den vorherigen Beiträgen beider Parteien entstanden war, aufgeteilt werden sollte und gaben an, was sie aus der Sicht der britischen Einwohner, die als unvoreingenommene Zuschauer agierten, für ihren gerechten Anteil hielten. Die Zuschaueraufteilung erhielten wir durch eine ergänzenden Umfrage. Wir stellten fest, dass die Verteilungsentscheidungen von Einheimischen und Einwanderern keine Eigengruppen-Voreingenommenheit zeigten. Ihre Entscheidungen waren jedoch egoistisch voreingenommen, da sie darauf hinwiesen, dass der Kuchen ausschließlich aus ihren eigenen Beiträgen entstanden war. Dieses Verhalten verschwand, wenn es dem Partner unverhältnismäßig schadete. Ihre Fairness-Überzeugungen zeigten Hinweise auf egozentrische Normübernahme: Sie bevorzugten Gleichheit als Beitragszahler und Gleichberechtigung als Nicht-Beitragszahler. Sie glaubten außerdem, dass Zuschauer negativ gegen Einwanderer und zugunsten von Einheimischen diskriminieren würden, aber diese Wahrnehmung war im Hinblick auf die Aufteilungen der Zuschauer unbegründet. Die Auswirkungen unserer Ergebnisse wurden in Kontext mit der Migrationsforschung und Integrationspolitik gesetzt.
Keywords: C99; D69; D91; J15; 330; redistribution; equity; equality; United Kingdom; contributions; ingroup bias; self-serving behavior; egocentric norms; fairness; natives; immigrants